Imaging techniques for assessment of inflammatory bowel disease: joint ECCO and ESGAR evidence-based consensus guidelines - Panes, Julian; Ehehalt, Robert (Journal of Crohn's and Colitis, 2013)
The management of patients with IBD requires evaluation with objective tools, both at the time of diagnosis and throughout the course of the disease, to determine the location, extension, activity and severity of inflammatory lesions, as well as, the potential existence of complications. Whereas endoscopy is a well-established and uniformly performed diagnostic examination, the implementation of radiologic techniques for assessment of IBD is still heterogeneous; variations in technical aspects and the degrees of experience and preferences exist across countries in Europe. ECCO and ESGAR scientific societies jointly elaborated a consensus to establish standards for imaging in IBD using magnetic resonance imaging, computed tomography, ultrasonography, and including also other radiologic procedures such as conventional radiology or nuclear medicine examinations for different clinical situations that include general principles, upper GI tract, colon and rectum, perineum, liver and biliary tract, emergency situation, and the postoperative setting. The statements and general recommendations of this consensus are based on the highest level of evidence available, but significant gaps remain in certain areas such as the comparison of diagnostic accuracy between different techniques, the value for therapeutic monitoring, and the prognostic implications of particular findings.
Gesehen am 16.12.2021